Buanglang kanpatiwat 2475 - Kulap Saipradit, 1905-1974. ([Bangkok] : Samnakphim Burapha Daeng, 1975)
On motives of leaders of 1932 coup in Thailand.
In Thai.
Keywords: Thailand -- History -- Coup d'état, 1932.